HUBUNGAN KESULITAN KEUANGAN DENGAN MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2016 - Feldo, Ferix; Rinaningsih, Rinaningsih; Yuliati, Retno (EQUITY, 2018)
This research aims to know how the relationship between financial distress as measured by manajemen laba using Discretionary value Accruals (DA). This research use quantitative approach and the population used is the all of company listed in the Indonesian Stock Exchange period 20102016. Research conducted using multiple linear regression. The result of the research indicate (1) there is a negative significant relationship between financial distress in distress1 category characterized by a negative net income during the current year with warnings management. (2) there is no significant relationship between financial distress in distress2 category characterized by negative working capital during the current year with manajemen laba, (3) there is on relationship between financial distress in distress3 category characterized by negative net income and working capital during the current year withmanajemen laba.